Evaluation of palatal dimensions in different facial patterns by using digital dental casts - Silvana Allegrini KAIRALLA; Leandro VELASCO; Andre Luis Lacerda BACHI; Lucia Hatsue YAMAMOTO; Mario CAPPELLETTE JR (Dental Press Editora, 2022)
ABSTRACT Objective: To analyze the variations of hard palate volume in adults with normal occlusion and different facial types and patterns, by using a three-dimensional analysis on digital casts. Methods: The dental casts of 70 Caucasian adults (28 men, 42 women), mean age of 16.4 years (SD 1.3 years), were scanned by using a tridimensional scanner (Delcam PowerSHAPE™, 2010, Birmingham, UK). Close points were selected in the gingival and cervical regions on the lingual surface of the maxillary teeth, to analyze palatal morphology. The facial patterns and types, and the measurements (width, length, height, volume) of the space on the hard palate were compared using analysis of covariance (ANCOVA), with age as the covariate, and sex as the independent variable. The significance level of 5% (p < 0.05) was adopted. Results: This study showed that the measurements of the width and length were similar among the mesofacial, dolichofacial and brachyfacial facial types, although the height and volume of the space on the hard palate were slightly smaller in dolichofacial individuals, and both Pattern I and Pattern II individuals showed no significant changes for the four measurements. The mean values among facial patterns were: Pattern I - width 38.31±2.59 mm; length 37.44±2.42 mm; height 17.03±2.42 mm and volume 10.52±1.72 mm3; Pattern II - width 37.48±2.44 mm; length 37.48±2.44 mm; height 16.79±2.42 mm and volume 10.41±1.65 mm3 (p>0.05 for all variables). Conclusion: There were no significant differences for the facial patterns and facial types of the individuals compared in the analyzed sample.